Tissue-Specific Function of Thyroid Hormone Transporters: New Insights from Mouse Models - Salveridou, Eva; Mayerl, Steffen; Sundaram, Sivaraj Mohana; Markova, Boyka; Heuer, Heike (Experimental and Clinical Endocrinology & Diabetes, 2019)
Thyroid hormone (TH) transporters are required for cellular transmembrane passage of TH and are thus mandatory for proper TH metabolism and action. Consequently, inactivating mutations in TH transporters such as MCT8 or OATP1C1 can cause tissue- specific changes in TH homeostasis. As the most prominent example, patients with MCT8 mutations exhibit elevated serum T3 levels, whereas their CNS appear to be in a TH deficient state. Here, we will briefly summarize recent studies of mice lacking Mct8 alone or in combination with the TH transporters Mct10 or Oatp1c1 that shed light on many aspects and pathogenic events underlying global MCT8 deficiency and also underscore the contribution of Mct10 and Oatp1c1 in tissue-specific TH transport processes. Moreover, development of conditional knock-out mice that allow a cell-specific inactivation of TH transporters in distinct tissues, disclosed cell-specific changes in TH signaling, thereby highlighting the pathophysiological significance of local control of TH action.
Keywords: T3; T4; Mct8; Allan-Herndon-Dudley syndrome; AHDS; Slc16a2; OATP1C1; Slco1c1; MCT10; Slc16a10